31 days before your CCNA security exam a day-by-day review guide for the IINS 210-260 certification exam - Gargano, Patrick (Cisco Press, 2016)
31 Days Before Your CCNA Security Exam 31 Days Before Your CCNA Security Exam offers you an engaging and practical way to understand the certification process, commit to taking the CCNA Security IINS 210-260 certification exam, and finish your preparation using a variety of Primary and Supplemental study resources. The IINS 210-260 exam tests your knowledge of secure network infrastructure, core security concepts, secure access, VPN encryption, firewalls, intrusion prevention, web/email content security, and endpoint security. It also tests your skills for installing, troubleshooting, and monitoring secure networks to maintain the integrity, confidentiality, and availability of data and devices. Sign up for the IINS 210-260 exam and use the book's day-by-day guide and checklist to organize, prepare, and review. Each day in this guide breaks down an exam topic into a manageable bit of information to review using short summaries. A Study Resources section provides you with a quick reference for locating more in-depth treatment of a day's topics within the Primary and Supplemental resources. The features of the book empower you to fit exam preparation into a busy schedule: · A visual calendar summarizing each day's study topic · A checklist providing advice for preparation activities leading up to the exam · A description of the CCNA Security IINS 210-260 exam organization and sign-up process · Strategies from the author to be mentally, organizationally, and physically prepared for exam day · A conversational tone, which makes your study time more enjoyable Primary Resources: CCNA Security 210-260 Official Cert Guide ISBN-13: 978-1-58720-566-8 CCNA Security Course Booklet Version 2 ISBN-13: 978-1-58713-351-0 CCNA Security Lab Manual Version 2 ISBN-13: 978-1-58713-350-3 Supplemental Resources: CCNA Security 210-260 Complete Video Course ISBN-13: 978-0-13-449931-4 CCNA Security Portable Command Guide , Second Edition ISBN-13: 978-1-58720-575-0 Cisco ASA: All-in-One Next-Generation Firewall, IPS, and VPN Services , Third Edition ISBN-13: 978-1-58714-307-6 Category: Certification Covers: CCNA Security.
Includes bibliographical references and index. - Online resource; title from PDF title page (EBSCO, viewed October 17, 2017)
Keywords: Electronic data processing personnel -- Study guides -- Certification; Computer networks -- Study guides -- Security measures -- Examinations; Réseaux d'ordinateurs; Sécurité; Mesures; Examens; Guides de l'étudiant; COMPUTERS; Certification Guides; General; Electronic data processing personnel; Certification; Computer networks; Security measures; Examinations; Study guides